Strategi Pengembangan Objek Wisata Ollon di Kabupaten Tana Toraja: (Studi Kasus : Lembang Bau, Kecamatan Bonggakaradeng) - Sry Juliansi; Murshal Manaf; Jufriadi Jufriadi (Journal of Urban Planning Studies, 2023)
This study aimed to analyze what factors cause the Ollon Tourism Object to not develop and to identify the strategy for developing Ollon Tourism Object. This research approach uses qualitative and quantitative approaches by collecting quantitative data which then uses Multiple Linear Regression analysis to measure what factors and how much influence the development of tourist objects then uses the SWOT analysis tool to identify strategies for developing tourist objects. The conclusion from this study is that there are two factors that have caused the Ollon Tourism Object in Lembang Bau, Bonggakaradeng District to not develop, including factors from infrastructure (telecommunication network conditions, electricity networks, garbage/waste networks, transportation networks) and accessibility (road network conditions). The conclusion from the results of the SWOT analysis to identify the strategy for developing the Ollon Tourism Object is in quadrant I between the SO strategy (strength-opportunity) by using all the strengths it has to take advantage of all the opportunities as much as possible.